2016
DOI: 10.1155/2016/2156148
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Pain in the Female Patient: A Case of Concurrent Acute Appendicitis and Ruptured Endometrioma

Abstract: General surgeons are often asked to evaluate acute abdominal pain which has an expanded differential diagnosis in women of childbearing age. Acute appendicitis accounts for many surgical emergencies as a common cause of nongynecologic pelvic pain. In some rare instances, acute appendicitis has been shown to occur simultaneously with a variety of gynecologic diseases. We report a case of concurrent acute appendicitis and ruptured ovarian endometrioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, overall, the advantages of laparoscopy are, at best, modest and clinical benefit is not always demonstrable. 19,21 Anyhow, we found in this study that laparoscopic appendicectomy proved nowadays is the most applicable and confident for difficult curious situations of inflammation and sequences of acute appendicitis with other intra-abdominal pathologies, as the laparoscopic appendectomy plays both diagnostic and therapeutic roles. 22,23 In these equivocal cases during laparoscopy, the process of laparoscopic appendectomy had been given another advantage to this approach which is also evidenced by Vettoretto and Agresta, 16 that they agreed that laparoscopy allows for superior visualization of the peritoneal cavity and exclusion of other pathology when the diagnosis of appendicitis is equivocal.…”
Section: Figure 1: Used Ports Sitesmentioning
confidence: 81%
See 1 more Smart Citation
“…However, overall, the advantages of laparoscopy are, at best, modest and clinical benefit is not always demonstrable. 19,21 Anyhow, we found in this study that laparoscopic appendicectomy proved nowadays is the most applicable and confident for difficult curious situations of inflammation and sequences of acute appendicitis with other intra-abdominal pathologies, as the laparoscopic appendectomy plays both diagnostic and therapeutic roles. 22,23 In these equivocal cases during laparoscopy, the process of laparoscopic appendectomy had been given another advantage to this approach which is also evidenced by Vettoretto and Agresta, 16 that they agreed that laparoscopy allows for superior visualization of the peritoneal cavity and exclusion of other pathology when the diagnosis of appendicitis is equivocal.…”
Section: Figure 1: Used Ports Sitesmentioning
confidence: 81%
“…10,12,16,19,20 In our study, we observed controversial cases of acute appendicitis with complicated ovarian cysts but histopathologically confirmed acute appendicitis, and this is established by many studies. 21,22 Furthermore, a study by Switzer, Gill and Karmali verified that laparoscopic appendectomy is practicable and has advantages over open appendectomy under certain interrogating circumstances. 19,20 These advantages are most evident in the young female, the working patient, and the obese patient.…”
Section: Figure 1: Used Ports Sitesmentioning
confidence: 98%